Pengaruh Jumlah Pelat Helical Terhadap Daya Dukung Tekan Pondasi Tiang Helical Pada Tanah Gambut Dengan Metoda Pembebanan Constant Stress Of Penetration - Usman, Fauzan; Fatnanta, Ferry; Nugroho, Soewignjo Agus (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The selection of the type of foundation is very influential on the strength of a building construction. One of the alternatives that can be used as a substitute for cerucuk foundationis helical pile foundation. Helical pile a manufactured steel foundation consisting of one or more helix-shaped bearing plates affixed to a central shaft that is rotated into the ground tosupport structures. This research presented result of static loading test constant stress of penetration method helical pile conducted at peat. Result of data from loading test in theform of load and settlement will be interpreted with tangent of intersection method, and Terzaghi and Peck method. The addition of helical plate under first helical does not give anyeffect on pile capacity if helical diameter is smaller, when a helical plate at the same diameter is added, the pile capacity increase. For empiric formula calculation of helical pilecapacities show that chylindrical shear closer to the results of loading test, with standard error of 1,06.Key words: helical pile, peat, individual plate bearing, cylinder shear